Blood circuit reconstruction in an abdominal mouse heart transplantation model - Yin, Decheng; Fu, Jian; Allabauer, Ida; Witzke, Oliver; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2021)
The surgical technique of heterotopic abdominal heart transplantation in mice is a standard model for research in transplantation immunology. Here, the established technique for a modified blood circuit reconstruction in a heterotopic abdominal heart transplantation model is presented. This method uses the intrathoracic inferior vena cava (IIVC) instead of the pulmonary artery of the donor heart for the anastomosis to the inferior vena cava of the recipient. It is facilitating and improving success rates for abdominal heart transplantation in mice.
CRIS-Team Scopus Importer:2021-07-02